Relationship Between the OF Classification and Radiological Outcome of Osteoporotic Vertebral Fractures After Kyphoplasty. Issue 4 (May 2022) - Palmowski, Yannick; Balmer, Sophie; Hu, Zhouyang; Winkler, Tobias; Schnake, Klaus John; Kandziora, Frank; Pumberger, Matthias
Study Design: Retrospective cohort study. Objectives: The OF classification is a new classification for osteoporotic vertebral fractures. The aim of this study was to clarify the relationship between preoperative OF subgroups and the postoperative outcome after kyphoplasty in patients with such fractures. Methods: Patients who underwent kyphoplasty of a single osteoporotic vertebral fracture were included and divided into groups according to the OF subgroups. Pre- and postoperative plain radiographs were analyzed in regard to the restoration of vertebral body height and local kyphotic angle (LKA). Additionally, clinical data including pre- and postoperative Visual Analogue Scale pain scores was documented. The clinical and radiological results were compared pre- and postoperatively within groups and between groups. Results: A total of 156 patients from OF subgroups 2 to 4 were included (OF 2: n = 58; OF 3: n = 36; OF 4: n = 62). Patients from all groups experienced significant pain relief postoperatively ( P < .001). Patients with OF 2 fractures showed a repositioning of the vertebral body height in the anterior and middle portions (both P < .001), but no significant improvement in LKA. For OF 3 and 4 fractures, there was a significant restoration of vertebral body height ( P < .001 for both) and a significant improvement of LKA ( P < .001 for both). The highest average restoration was noted in the OF 4 group. Conclusions: A higher OF subgroup is related to a higher radiological benefit from kyphoplasty. This confirms that the OF classification is an appropriate tool for the preoperative assessment of osteoporotic fractures.